Medical Risk in Logistic and Production Systems - Katarzyna KOSAKOWSKA; Dominik ŁODEJ; Grzegorz SOBECKI; Robert PAWLICKI (Communications of International Proceedings, 2021)
The COVID-19 pandemic made the world aware that medical risk is one of the most significant risks in existence. The very strong impact of a pandemic on logistics systems is also undeniable. Logistics systems of hospitals are the ones that are stressed the most, but those of manufacturing companies have undoubtedly been equally affected. The paper deals with the analysis of medical risks associated with the current global situation and describes examples of methods for managing such risks in logistics systems.
Keywords: Medical Risk; Logistics Systems; Risk Management.